Mucosal and salivary microbiota associated with recurrent aphthous stomatitis. Issue 1 (December 2016) - Kim, Yun-ji; Choi, Yun; Baek, Keum; Yoon, Seok-Hwan; Park, Hee; Choi, Youngnim
Abstract Background Recurrent aphthous stomatitis (RAS) is a common oral mucosal disorder of unclear etiopathogenesis. Although recent studies of the oral microbiota by high-throughput sequencing of 16S rRNA genes have suggested that imbalances in the oral microbiota may contribute to the etiopathogenesis of RAS, no specific bacterial species associated with RAS have been identified. The present study aimed to characterize the microbiota in the oral mucosa and saliva of RAS patients in comparison with control subjects at the species level. Results The bacterial communities of the oral mucosa and saliva from RAS patients with active lesions (RAS, n  = 18 for mucosa andn  = 8 for saliva) and control subjects (n  = 18 for mucosa andn  = 7 for saliva) were analyzed by pyrosequencing of the 16S rRNA genes. There were no significant differences in the alpha diversity between the controls and the RAS, but the mucosal microbiota of the RAS patients showed increased inter-subject variability. A comparison of the relative abundance of each taxon revealed decreases in the members of healthy core microbiota but increases of rare species in the mucosal and salivary microbiota of RAS patients. Particularly, decreasedStreptococcus salivarius and increasedAcinetobacter johnsonii in the mucosa were associated with RAS risk. A dysbiosis index, which was developed using the relative abundance ofA. johnsonii andS. salivarius and the regression coefficients, correctly predicted 83 % of the total cases for the absence or presence of RAS. Interestingly, A. johnsonii substantially inhibited the proliferation of gingival epithelial cells and showed greater cytotoxicity against the gingival epithelial cells thanS. salivarius. Conclusion RAS is associated with dysbiosis of the mucosal and salivary microbiota, and two species associated with RAS have been identified. This knowledge may provide a diagnostic tool and new targets for therapeutics for RAS.